Refugees and Religion Ethnographic Studies of Global Trajectories - Meyer, Birgit; van der Veer, Peter (Bloomsbury Academic, 2021)
Understanding religion from a material and corporeal angle, this open access book addresses the ways in which refugees practice their religions and convert or develop new faiths. It also evaluates how secular institutions in Europe frame and determine what is classified as religion according to the law, and delineate the limits of religious authority, religious practice, and religious speech. The question of nationalism and migration has been shaping the political landscape in Europe for more than a decade, resulting in a nationalist upsurge. This volume places the current trajectories of people from Asia and Africa who flee from conditions such as oppression and conflict, and who are seeking refuge in Europe in a broader historical and comparative perspective. In so doing, it addresses past experiences in Europe with the role of religion in both producing and accommodating refugees, in the aftermath of the Peace of Westphalia, World War II, and in the context of the Cold War.